2022
DOI: 10.3390/cancers14194791
|View full text |Cite
|
Sign up to set email alerts
|

Anoikis-Associated Lung Cancer Metastasis: Mechanisms and Therapies

Abstract: Tumor metastasis occurs in lung cancer, resulting in tumor progression and therapy failure. Anoikis is a mechanism of apoptosis that combats tumor metastasis; it inhibits the escape of tumor cells from the native extracellular matrix to other organs. Deciphering the regulators and mechanisms of anoikis in cancer metastasis is urgently needed to treat lung cancer. Several natural and synthetic products exhibit the pro-anoikis potential in lung cancer cells and in vivo models. These products include artonin E, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 179 publications
(249 reference statements)
0
28
0
Order By: Relevance
“…Cancer cells could overcome anoikis which would contribute to tumor progression, metastasis, and resistance of therapy (21). Previous studies (13,22) have demonstrated that anoikis plays great roles in the development of lung cancer. Cellular retinoic acid binding protein 2 (CRABP2) was shown to promote integrin β1/FAK/ERK signaling and inhibit anoikis; overexpressed CRABP2 was found to increase lymph node and liver metastasis through in vivo tail vein injection of lung cancer cell models (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cells could overcome anoikis which would contribute to tumor progression, metastasis, and resistance of therapy (21). Previous studies (13,22) have demonstrated that anoikis plays great roles in the development of lung cancer. Cellular retinoic acid binding protein 2 (CRABP2) was shown to promote integrin β1/FAK/ERK signaling and inhibit anoikis; overexpressed CRABP2 was found to increase lymph node and liver metastasis through in vivo tail vein injection of lung cancer cell models (23).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors including Ras family, PI3K/AKT pathway and extracellular matrix adhesion can regulate anoikis. Controlling these factors to activate anoikis has been an important avenue for tumor therapy (13)(14)(15). Resistance to anoikis may also be an important reason of resistance to radiotherapy and chemotherapy in tumors (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…When loss of either cell adhesion or improper adhesion to ECM occurs, normal epithelial cells losing contact with ECM would rapidly undergo apoptosis, which is called anoikis [ 30 ]. Anoikis is a specific PCD pathway initiated by the detachment of cells from ECM playing an important role in body development, tissue homeostasis and sickness development [ 31 ]. However, the primary characteristic of tumor development is the ability to transform cells in “independent” growth conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) participate in multiple biological processes and regulate physiological functions ( 12 ). Anoikis is a specialized form of programmed apoptosis that occurs in two model epithelial cell lines when cell adherence to the ECM is lost or cell–matrix interactions are disrupted ( 13 , 14 ). Anoikis resistance is a property that cancer cells can acquire, allowing them to grow and spread from their primary sites to distant organs ( 15 ).…”
Section: Introductionmentioning
confidence: 99%